1958
DOI: 10.1524/zpch.1958.16.3_6.257
|View full text |Cite
|
Sign up to set email alerts
|

The Thermal Conductivity of Solid Hydrogen

Abstract: The author would like to express his thanks and appreciation to Professor C. F. Mate for his guidance and support in the completion of this work. The advice and assistance of Professor J. R. Gaines are especially appreciated, for if he had not provided the hydrogen samples, this work would never have been done. The author is also grateful to Mr. William Baker and his staff for technical assistance; to Mr. Larry Wilkes for the line drawings; and to Mr. James Constable, whose measurement of the ortho-hydrogen co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1973
1973
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…p = 6(g)Y2o(tO ) (1) where to describes the orientation of the ortho-hydrogen molecule with respect to the intermolecular axis,…”
Section: Ortho-hydrogen Singlesmentioning
confidence: 99%
“…p = 6(g)Y2o(tO ) (1) where to describes the orientation of the ortho-hydrogen molecule with respect to the intermolecular axis,…”
Section: Ortho-hydrogen Singlesmentioning
confidence: 99%
“…4 The first measurements of the thermal conductivity of solid hydrogen, which were performed in Ref. 5, revealed a strong dependence of the thermal conductivity of solid orthoparahydrogen solutions on the content of the ortho modification in the sample. Subsequent measurements 6 showed that the additional thermal resistivity due to the orthomolecules exhibits a temperature dependence close to T -3 and a quadratic concentration dependence.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, a defect-free pure p-H 2 crystal has a very high thermal conductivity. [6][7][8][9] The introduction of even small amounts of molecular or atomic impurity decreases strongly the value and temperature dependence of the thermal conductivity K(T) at temperatures near the phonon peak. [9][10][11] The main source of phonon scattering is the dynamic disorder produced in the crystal by the sharp mass difference between the substitution impurity and the matrix molecule.…”
mentioning
confidence: 99%